Dialekte machen - Schiesser, Alexandra (Linguistik - Impulse & Tendenzen, 2020)
This empirical study examines the importance of dialect and dialect use in Switzerland. Based on interdisciplinary approaches, it explores the extent to which linguistic perception and assessment on the part of laypersons is connected to actual language use. It shows that dialects are constructed by means of discursive processes and reproduced in language use. In this way, it illuminates how speakers create dialects.